(untitled) (Conference on English Language Teaching, 2023)
A euphemism is a word that can be used to transform an offensive or harsh phrase that may be mentioned or uttered in a political context into a pleasant expression that can be more acceptable to anyone who hears it, or in other words, a phrase that the listener can also accept. Then, this research aimed to analyze the types of euphemism in political context on Obama’s speech about “the state of American democracy”. Since the data were in the form of text, the research was of the descriptive variety. Based on Obama’s address, the data would be descriptively examined. For this study, which sought to describe several euphemisms used in Obama’s address about American democracy, a descriptive methodology was applicable. The data was then gathered by the researcher using Obama’s speech’s transcript. The data showed that from 9 types of euphemism, metaphor was the most found in the speech.